Manajemen Sumber Daya Manusia Tenaga Pendidik dan Kependidikan Di TK Al-Aqsha Kota Jambi - K.A. Rahman; Verdianto Verdianto; Bresman Jonathan Valentino Hutagalung; Anggi Netia; Magh Fira; Wila Yurnita; Herlina Oktapiani (Jurnal Ilmiah Dikdaya, 2023)
This study aims to provide insights related to PAUD management to readers, observers, academics, and education practitioners to understand how comparisons are made from various perspectives regarding the human resources of educators and educational staff in PAUD institutions. This research was conducted at Al-Aqsa Kindergarten Jl. Captain A Hasan, Pematang Sulur, Telanaipura District, Jambi City. The time for this research to be conducted was November 2, 2022. This research is a qualitative descriptive research, namely the research method used to examine the natural conditions of objects. Data collection techniques are triangulation (combined), data analysis is inductive/qualitative in nature, and the results of qualitative research emphasize meaning rather than generalization. The approach uses a qualitative approach, namely an approach that describes the data descriptively. The results of this study are that the school's efforts to improve human resource management are quite good, this can be seen by the academic atmosphere that is well organized, where this school is still relatively new but has shown good quality, this is evidenced by the large number of students with a large number of students. balanced teachers and the enthusiasm of the community to send their children to the school, where all staff are people who have met the qualifications to work according to their respective job descriptions